The Welfare State as Universal Social Security: A Global Analysis - Öktem, Kerem Gabriel (Social Inclusion, 2020)
Over the past decades, the geography of comparative welfare state research has transformed. Whereas scholars used to focus on a limited number of advanced industrialised democracies, they now increasingly study developments in Europe’s periphery, East Asia, and Latin America. So, does this mean that the welfare state has spread around the world? To answer this question, we analyse different ways to measure welfare states and map their results. With the help of International Labour Organization and International Monetary Fund data, we explore measurements based on social expenditures, social rights, and social security legislations and show that each of them faces serious limitations in a global analysis of welfare states. For some measurements, we simply lack global data. For others, we risk misclassifying the extent and quality of some social protection systems. Finally, we present a measurement that is grounded in the idea that the welfare state is essentially about universalism. Relying on a conceptualisation of the welfare state as collective responsibility for the wellbeing of the entire population, we use universal social security as a yardstick. We measure this conceptualization through health and pension coverage and show that a growing number of countries have become welfare states by this definition. Yet, it is possible that at least some of these cases offer only basic levels of protection, we caution.